On Some Peculiarities of Teaching English in the NKR High Schools - Babayan, Angela (Լիմուշ հրատ.)
This article discusses the peculiarities of the English language teaching in the NKR high schools. In particular, the analysis of the EL audience by means of SWOT-structure is presented. In addition, the main content of EL teaching in high school is viewed and key strategies of productive learning are suggested. В данной статье рассматриваются особенности преподавания английского языка в старших школах НКР. В частности, представляется анализ контингента учащихся с использованием SWOT-корпуса. Кроме того, рассматривается основное содержание обучения английскому языку в старшей школе и предлагаются ключевые стратегии продуктивного обучения. Այս հոդվածում քննարկվում է անգլերենի դասավանդման առանձնահատկությունները ԼՂՀ ավագ դպրոցներում: Մասնավորապես ներկայացվում են անգլերեն սովորողների քանակակազմի վերլուծությունները SWAT-կառույցի միջոցով: Բացի այդ` քննարկվում է ավագ դպրոցում անգլերենի ուսուցման հիմնական բովանդակությունը և առաջարկվում են արդյունավետ ուսուցման ռազմավարություններ:
Keywords: High school education